Evaluation of resource creations accuracy by using sentiment analysis - Mohamad Hardyman, Barawi; Yet, Yong Seng (Elsevier Ltd., 2013)
Opinionated texts in various social media can be further processed using sentiment analysis to generate a sentiment polarity reading. This reading shows the general public view toward a product for both developer and user. However, the task is difficult due to the dynamic changes in these texts. The purpose of this paper is to evaluate the capability of existing dictionaries (resource creations) to analyse the opinionated comments from an online learning video.